ErbB2 and p38γ MAPK mediate alcohol-induced increase in breast cancer stem cells and metastasis. Issue 1 (December 2016) - Xu, Mei; Ren, Zhenhua; Wang, Xin; Comer, Ashley; Frank, Jacqueline; Ke, Zun-ji; Huang, Yi; Zhang, Zhuo; Shi, Xianglin; Wang, Siying; Luo, Jia
Abstract Background Both epidemiological and experimental studies suggest that excessive alcohol exposure increases the risk for breast cancer and enhances metastasis/recurrence. We have previously demonstrated that alcohol enhanced the migration/invasion of breast cancer cells and cancer cells overexpressing ErbB2/HER2 were more sensitive to alcohol exposure. However, the underlying mechanisms remain unclear. This study was designed to investigate the mechanisms underlying alcohol-enhanced aggressiveness of breast cancer. Cancer stem cells (CSCs) play a critical role in cancer metastasis and recurrence. Methods We evaluated the effect of chronic alcohol exposure on mammary tumor development/metastasis in MMTV-neu transgenic mice and investigated the cell signaling in response to alcohol exposure in breast cancer cells overexpressing ErbB2/HER2. Results and discussion Chronic alcohol exposure increased breast cancer stem cell-like CSC population and enhanced the lung and colon metastasis in MMTV-neu transgenic mice. Alcohol exposure caused a drastic increase in CSC population and mammosphere formation in breast cancer cells overexpressing ErbB2/HER2. Alcohol exposure stimulated the phosphorylation of p38γ MAPK (p-p38γ) which was co-localized with phosphorylated ErbB2 and CSCs in the mammary tumor tissues. In vitro results confirmed that alcohol activated ErbB2/HER2 and selectively increased p-p38γ MAPK as well as the interaction between p38γ MAPK and its substrate, SAP97. However, alcohol did not affect the expression/phosphorylation of p38α/β MAPKs. In breast cancer cell lines, high expression of ErbB2 and p-p38γ MAPK was generally correlated with more CSC population. Blocking ErbB2 signaling abolished heregulin β1- and alcohol-stimulated p-p38γ MAPK and its association with SAP97. More importantly, p38γ MAPK siRNA significantly inhibited an alcohol-induced increase in CSC population, mammosphere formation and migration/invasion of breast cancer cells overexpressing ErbB2. Conclusions p38γ MAPK is downstream of ErbB2 and plays an important role in alcohol-enhanced aggressiveness of breast cancer. Therefore, in addition to ErbB2/HER2, p38γ MAPK may be a potential target for the treatment of alcohol-enhanced cancer aggressiveness.